PENGARUH LINGKUNGAN KELUARGA, SEKOLAH DAN FASILITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA PADA SMK NEGERI 1 TIDORE - Djumati, Ali (EDUKASI, 2017)
The aim of this research is to analyse the existence of environmental influence of family, and school learning facility to achievement learn student at SMKN 1 Tidore. This Research use collected primary processing through quisioner passed to 127 responden taken as sampel.The method of this research is descriptive analysis for the explanation of students’ environmental of family (X1), environmental of school (X2), and Learning Facility (X3) to learning achievement (Y). Data analysis used doubled linear regression of model to know bigly of influence of the free variable to students’ learning achievement (Y).The result of this research by using regression (Test t) with family environmentf (X1) assess t-statistik equal to 2,005 with signifikan equal to 0,047. Environmental of school (X2) has an effect signifikan to students’ learning achievement and there are relation which are positive with score of t-statistik equal to 2,300 with signifikan equal to 0,023 whereas Facility variable Learn (X3) assess t-statistik equal to 2,870 storey level of signifikan 0,005. Whereas result of analysis of  regresiion of environmental of family variable, environmental of Facility and school Learn to achievement learn student is 15,747.  While with storey level of signifikan equal to 0,000. Result of this research is expected by old fellow can improve the quality of the way of educating its childs by paying attention regularity of students in learning at home. So, the students was motivated when learning at home. Keyword : Environmental of Family, Environmental of School, Learning Facility, Students Achievement